Action Plans in Patients Presenting to Emergency Departments with Asthma Exacerbations: Frequency of Use and Description of Contents. Issue 6 (2014) - Cross, Elfriede; Villa-Roel, Cristina; Majumdar, Sumit R; Bhutani, Mohit; Rosychuk, Rhonda J; Couperthwaite, Stephanie; Rowe, Brian H
Abstract : BACKGROUND: Although underused, written asthma action plans (AAPs) are associated with reduced numbers of emergency department (ED) visits and hospitalizations. OBJECTIVE: To describe the frequency of use and contents of any AAPs reported by patients presenting with exacerbations to three urban Canadian EDs. METHODS: Prospective data were collected through ED interview and chart review. Descriptive analyses used proportions and medians with interquartile range; multivariable logistic regression was used for the adjusted analyses. RESULTS: Among 176 enrolled patients, the median age was 27 years (interquartile range 23 to 39 years) and 97 (55%) were female. Few (n=42 [24%]) reported having AAPs at ED presentation and only six were written. Most (n=35 [75%]) patients with any AAP took action before the ED visit; none used a valid anti-inflammatory strategy. The first step of 27 plans was to increase asthma medication; no patients appropriately increased inhaled corticosteroids (ICS). In multivariable analyses, only the use of either ICS or ICS/long-acting β-agonist combination agents (31% had AAPs versus 12% did not have AAPs (adjusted OR 3.0 [95% CI 1.14 to 8.07]) and asthma education (47% had AAPs versus 21% did not have AAPs, adjusted OR 3.2 [95% CI 1.13 to 9.19]) were independently associated with AAP possession. CONCLUSION: Possession of AAPs among patients presenting to the ED with acute asthma was low, and only one in 10 AAPs were written. Patients who reported having any AAP used ineffective strategies to abort or mitigate the severity of an ED visit. Increasing frequency of written AAPs and improving their contents holds immediate promise in improving outcomes related to asthma.